Geodiversity: a significant, multi-faceted and evolving, geoscientific paradigm rather than a redundant term - Gray, Murray (Proceedings of the Geologists' Association, 2021)
Using outlines of ten geodiversity-related topics plus some related studies, this paper argues that geodiversity has contributed to many new insights, new avenues of research and new results. The ten topics are: Celebrating, Assessment and Measurement, Geosystem Services, Biodiversity, Geomaterials, Geotourism and Leisure, Geoheritage, National Geoconservation, World Heritage Sites and Global Geoparks, and Sustainability. It is concluded that geodiversity is a) a global, as well as regional/local concept, b) more than just related to biodiversity, important though that is, c) absolutely central to any relationship between the geology-related topics (‘Gs’). It is therefore argued that geodiversity is not a ‘redundant term’ as recently suggested but instead is a significant, multi-faceted and evolving, geoscientific paradigm.